DNA synthesis - dependent cell division of Escherichia coli 15 TAU after arginine and uracil starvation - Lhotská, M; Vondrejs, V (Folia microbiologica, 1975)
Extensive cell division after synchronization of Escherichia coli 15 TAU by arginine and uracil starvation occurs only when DNA synthesis is permitted to proceed by at least a short pulse of thymine applied between 30 and 60 min after transfer of synchronized culture to thymine-free medium with arginine and uracil. The time schedule of synchronized cell division in dependence on the schedule of intervals of DNA synthesis and inhibition of DNA synthesis was determined. The termination of replication cycles which were not completed to the very end during arginine and uracil starvation seems to be the decisive event for subsequent cell division after synchronization.
Keywords: kolorimetrie; Cell Division; DNA bakterií; kyselina oxolinová; kyselina nalidixová; mutace; Thymine; počet buněk; Escherichia coli; thymin; uracil; časové faktory; Arginine; Oxolinic Acid; DNA Replication; DNA, Bacterial; replikace DNA; Nalidixic Acid; arginin; Colorimetry; Uracil; Mutation; Time Factors; Cell Count; buněčné dělení